A bottom-up approach for cultural tourism management in the old city of As-Salt, Jordan. Issue 1 (6th February 2017) - Jamhawi, Monther M.; Hajahjah, Zain A.
Abstract : Purpose: The purpose of this paper is to present a "bottom-up approach" for cultural tourism management in the old city of As-Salt in Jordan. The city of As-Salt has unique historic buildings that represent Jordan's traditional urban life; however, it is rarely promoted in the tourism map of Jordan. Design/methodology/approach: This paper assessed the existing local policies and strategies dealing with the case of As-Salt, and reviewed some other international and regional case studies. The method adopted included semi-structured interviews and designated questionnaires directed to the most relevant stakeholders and visitors. The assessment process depended on "Integrated Cultural Heritage Management Approach" in order to identify the parameters that needed to be considered while planning for a sustainable management approach in the city. Findings: The results showed many managerial problems and gaps in dealing with the core of the city as a tourist attraction. Results and recommendations mainly relied on the need for an entity to be an official umbrella to guide the relationship between heritage protection and tourism development in the city. A new scenario of tourist itineraries in the city is presented with new idea of developing cultural events and activities. Originality/value: No similar prior studies were carried out in As-Salt that are tackling this subject. And it is hoped that this approach will lead and guide other similarly situated destinations as they develop plans and approaches for their cities.